Epidemiology of canine ehrlichiosis and molecular characterization of Erhlichia canis in Bangladeshi pet dogs. - Ajran Kabir; Chandra Shaker Chouhan; Tasmia Habib; Md Zawad Hossain; Abu Raihan; Farzana Yeasmin; Mahbubul Pratik Siddique; A K M Anisur Rahman; Azimun Nahar; Md Siddiqur Rahman; Md Amimul Ehsan (PLoS ONE)
Background Ehrlichia canis, a rickettsial organism, is responsible for causing ehrlichiosis, a tick-borne disease affecting dogs. Objectives This study aimed to estimate ehrlichiosis prevalence and identify associated risk factors in pet dogs. Methods A total of 246 peripheral blood samples were purposively collected from pet dogs in Dhaka, Mymensingh, and Rajshahi districts between December 2018 and December 2020. Risk factor data were obtained through face-to-face interviews with dog owners using a pre-structured questionnaire. Multivariable logistic regression analysis identified risk factors. Polymerase chain reaction targeting the 16S rRNA gene confirmed Ehrlichia spp. PCR results were further validated by sequencing. Results The prevalence and case fatality of ehrlichiosis were 6.9% and 47.1%, respectively. Dogs in rural areas had 5.8 times higher odds of ehrlichiosis (odd ratio, OR: 5.84; 95% CI: 1.72-19.89) compared to urban areas. Dogs with access to other dogs had 5.14 times higher odds of ehrlichiosis (OR: 5.14; 95% CI: 1.63-16.27) than those without such access. Similarly, irregularly treated dogs with ectoparasitic drugs had 4.01 times higher odds of ehrlichiosis (OR: 4.01; 95% CI: 1.17-14.14) compared to regularly treated dogs. The presence of ticks on dogs increased ehrlichiosis odds nearly by 3 times (OR: 3.02; 95% CI: 1.02-8.97). Phylogenetic analysis, based on 17 commercially sequenced isolates, showed different clusters of aggregation, however, BAUMAH-13 (PP321265) perfectly settled with a China isolate (OK667945), similarly, BAUMAH-05 (PP321257) with Greece isolate (MN922610), BAUMAH-16 (PP321268) with Italian isolate (KX180945), and BAUMAH-07 (PP321259) with Thailand isolate (OP164610). Conclusions Pet owners and veterinarians in rural areas should be vigilant in monitoring dogs for ticks and ensuring proper preventive care. Limiting access to other dogs in high-risk areas can help mitigate disease spread. Tick prevention measures and regular treatment with ectoparasitic drugs will reduce the risk of ehrlichiosis in dogs. The observed genetic similarity of the Bangladeshi Ehrlichia canis strain highlights the need for ongoing surveillance and research to develop effective control and prevention strategies, both within Bangladesh and globally.